2017
DOI: 10.1007/s10393-017-1234-0
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Leptospirosis in Malaysia

Abstract: Leptospirosis is a bacterial disease transmitted to humans and animals by direct or indirect contact with urine or body fluids from infected animals especially rodents. Infection can be associated with wide clinical spectrum varying from asymptomatic to severe multi-organ syndrome with life-threatening consequences. We conducted a review of published studies on incidences, case reports, sero-epidemiological surveys from year 2000 to 2015 using different electronic data bases. Our study revealed that majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…The hospital was selected because it is in Serdang, a district in the state of Selangor, the most populous state in Malaysia (Department of Statistic Malaysia 2015). In July 2015, the Selangor state had the fourth highest number of reported cases after Kuala Lumpur, Negeri Sembilan, and Sarawak (Garba et al 2017). Khairani-Bejo et al (2004) reported 3.1% prevalence of leptospirosis among rats that were caught in Serdang residential area.…”
Section: Methodsmentioning
confidence: 99%
“…The hospital was selected because it is in Serdang, a district in the state of Selangor, the most populous state in Malaysia (Department of Statistic Malaysia 2015). In July 2015, the Selangor state had the fourth highest number of reported cases after Kuala Lumpur, Negeri Sembilan, and Sarawak (Garba et al 2017). Khairani-Bejo et al (2004) reported 3.1% prevalence of leptospirosis among rats that were caught in Serdang residential area.…”
Section: Methodsmentioning
confidence: 99%
“…Arbitrary values of the initial conditions were set, but a human:infected rodent ratio of 1:3 was chosen, according to the information documented in several works [32,[49][50][51]. Time and parameters are expressed in day and 1/day, respectively.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The duration of immunity is also said to range from six months to three years depending on the choice of adjuvants 17 18 . Recent reports in the United States indicate up to 30 per cent of vaccinated dogs do not respond to vaccinations and immunizations are also associated with adverse effects 10 . This is attributed to change in the epidemiology of the disease and ingress of new serovars in endemic areas.…”
Section: Leptospirosis Vaccinesmentioning
confidence: 99%
“…In the past century, several epidemics have been reported worldwide including India, where the disease has been endemic since the 20 th century 9 . Epidemiological investigations indicate that the infection is commonly associated with certain occupational groups such as farmers, sewage workers, veterinarians, and animal handlers 10 11 12 and most of the circulating serovars reside in rodents and other domestic animal reservoirs such as dogs, pigs and cattle 13 14 15 . Hence, these domestic animals may be the source of both human and animal infection.…”
mentioning
confidence: 99%